(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
This article presents the research of risk management in the enterprise. Posted definition of «economic risk» and «risk management» are principles of effective risk management system. There are presented and described the stages of the management process, namely: identification of risks; qualitative risk assessment; quantitative assessment; planning responses to the risks and monitor and control risks. The basic indicators of quantitative risk assessment are described: expectation, standard deviation, variance, coefficient of variation. Main ways to minimize risks in the enterprise are characterized in the article: security risk hedging liability insurance, diversification, risk sharing, backup tools, limitation, quality of manufactured products, business planning, management consulting.